Beliefs about fetal alcohol spectrum disorder among men and women at alcohol serving establishments in South Africa. - Eaton, Lisa A; Pitpitan, Eileen V; Kalichman, Seth C; Sikkema, Kathleen J; Skinner, Donald; Watt, Melissa H; Pieterse, Desiree; Cain, Demetria N (The American journal of drug and alcohol abuse, 2014)
South Africa has one of the highest rates of fetal alcohol spectrum disorder (FASD) in the world. However, little is known about what men and women who attend alcohol serving establishments believe about alcohol use during pregnancy and how these beliefs may be related to alcohol use.
Keywords: Adult; Alcohol Drinking; Female; Fetal Alcohol Spectrum Disorders; Health Behavior; Health Knowledge, Attitudes, Practice; Humans; Male; Pregnancy; Pregnant Women; Questionnaires; Risk-Taking; Self Report; South Africa; Young Adult